New Media dan Penguatan Moderasi Beragama di Indonesia - Hasan Sazali; Ali Mustafa (Program Studi Ilmu Komunikasi, 2023)
This article aims to analyze the use of YouTube in an effort to strengthen religious moderation in Indonesia on the official YouTube account of the Ministry of Religion of the Republic of Indonesia,